Analysis of the Impact of Investment Attractiveness on The Socio-Economic Development of the Bustan District of the Andijan Region - Khoshimov Sabir Murtazaevich (European Science Publishing, 2023)
The article discusses the role and importance of the attractiveness of the investment environment in the socio-economic development of the regions of our republic, the existing problems, analytical data, conclusions, suggestions and recommendations in this regard.
Keywords: investment attractiveness, investments, infrastructure facilities, franchise, business incubator, innovation potential, investment activity.